Genetikai teszt a fogyasztók számára - Tárczy, Edit Zsuzsanna (Debreceni Jogi Műhely, 2013)
The European Academies Science Advisory Council (hereafter: EASAC) and the Federationof European Academies of Medicine (hereafter: FEAM) published a study on „Direct-toconsumergenetic testing for health-related purposes in the European Union” in the summer of2012.This paper shows the results of the research of the working group of the two mentionedorganizations. The main aim was to investigate the scientific, ethic questions and thequestions in connection with the possible regulation. The second aim was to define principlesand recommendations for the European Commission, the European Parliament, the Council ofMinisters and the political decision-makers of the Member States.This paper also shows the results of the workshop – organized by the EASAC, the FEAM andthe Science and Technology Options Assessment (hereafter: STOA) - in the end of 2012.Finally, there are some facts on the regulations on the genetic tests outside the EU.